Nab‐paclitaxel‐based compared to docetaxel‐based induction chemotherapy regimens for locally advanced squamous cell carcinoma of the head and neck. (26th January 2015) - Schell, Amy; Ley, Jessica; Wu, Ningying; Trinkaus, Kathryn; Wildes, Tanya Marya; Michel, Loren; Thorstad, Wade; Gay, Hiram; Lewis, James; Rich, Jason; Diaz, Jason; Paniello, Randal C.; et al.
Abstract We previously reported that nab‐paclitaxel‐based induction chemotherapy (IC) and concurrent chemoradiotherapy resulted in low relapse rates (13%) and excellent survival in head and neck squamous cell carcinoma (HNSCC). We compare the disease‐specific survival (DSS) and overall survival (OS) between patients given nab‐paclitaxel, cisplatin, and fluorouracil with cetuximab (APF‐C) and historical controls given docetaxel, cisplatin, and fluorouracil with cetuximab (TPF‐C). Patients with locally advanced HNSCC were treated with APF‐C (n = 30) or TPF‐C (n = 38). After 3 cycles of IC, patients were scheduled to receive cisplatin concurrent with definitive radiotherapy. T and N classification and smoking history were similar between the two groups and within p16‐positive and p16‐negative subsets. The median duration of follow‐up for living patients in the APF‐C group was 43.5 (range: 30–58) months versus 52 (range: 13–84) months for TPF‐C. The 2‐year DSS for patients treated with APF‐C was 96.7% [95% Confidence Interval (CI): 85.2%, 99.8%] and with TPF‐C was 77.6% (CI: 62.6%, 89.7%) (P = 0.0004). Disease progression that resulted in death was more frequent in the TPF‐C group (39%) compared with the APF‐C group (3%) when adjusted for competing risks of death from other causes (Gray's test, P = 0.0004). In p16 positive OPSCC, the 2‐year DSS for APF‐C was 100% and for TPF‐C was 74.6% (CI: 47.4%, 94.6%) (P = 0.0019) and the 2‐year OS for APF‐C was 94.1% (CI: 65.0%, 99.2%) and for TPF‐C was 74.6% (CI: 39.8%, 91.1%) (P = 0.013). In p16 negative HNSCC, the 2‐year DSS for APF‐C was 91.7% (CI: 67.6%, 99.6%) and for TPF‐C was 82.6% (CI: 64.4%, 94.8%) (P = 0.092). A 2‐year DSS and OS were significantly better with a nab‐paclitaxel‐based IC regimen (APF‐C) compared to a docetaxel‐based IC regimen (TPF‐C) in p16‐positive OPSCC.